2014
DOI: 10.3174/ajnr.a4143
|View full text |Cite
|
Sign up to set email alerts
|

Silk Flow-Diverter Stent for the Treatment of Intracranial Aneurysms: A Series of 58 Patients with Emphasis on Long-Term Results

Abstract: BACKGROUND AND PURPOSE:The Silk flow-diverter stent is increasingly used to treat complex intracranial aneurysms including wide-neck, fusiform aneurysms. Sparse data are available concerning long-term results of this technique. We report our 5-year experience with Silk stent treatment of intracranial aneurysms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
39
0
6

Year Published

2015
2015
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(50 citation statements)
references
References 19 publications
5
39
0
6
Order By: Relevance
“…In our series we were able to achieve an approximately 80 percent occlusion rate. This result compares favorably to results of the previous reports utilizing the non-tapered version of these stents (3,12). Considering the larger size of the aneurysms (mean size larger than 13 mm) in our series, as a matter of fact, our occlusion …”
Section: █ Discussionsupporting
confidence: 76%
“…In our series we were able to achieve an approximately 80 percent occlusion rate. This result compares favorably to results of the previous reports utilizing the non-tapered version of these stents (3,12). Considering the larger size of the aneurysms (mean size larger than 13 mm) in our series, as a matter of fact, our occlusion …”
Section: █ Discussionsupporting
confidence: 76%
“…Furthermore, morbidity and mortality rates are similar to those reported in other series in the literature. 5,17,18,23 Finally, it is worth noting that the retrospective study design, small number of included cases, and prevalence of aneurysms of the ICA siphon (83%) and small aneurysms (78%) could represent certain limitations.…”
mentioning
confidence: 99%
“…The incidence of ISS was 5% in Murthy et al systematic review [56]. However, Lubicz et al [63] and Cohen et al [80] focused on this phenomenon and reported a higher rate of stenosis (57 and 38%, respectively). More interesting in Lubicz et al series is that 60% of these stenoses improved or disappeared in the long-term follow-up.…”
Section: Stenosis and Paomentioning
confidence: 94%
“…Eight studies [36,55,[57][58][59][60][61][62] with 285 patients and 317 IAs were included. In this review, complete occlusion was [63] have published their 5-year experience with SFD and they could compare the rate of complication associated with the use of the first and the second SFD generation (Silk +). Between July 2009 and May 2014, all patients (58 patients with 70 aneurysms) treated with SFD were included.…”
Section: Clinical Profile and Completed Studiesmentioning
confidence: 99%